The Contribution Of The Black Minorities In The American Economic And Political Life During Obama Presidency - Messaoudi Amina, Layachi Hadjer (UNIVERSITY MOHAMED BOUDIAF - M’SILA, 2021)
This work outlines some of the most important information about Barack Obama, his biography and how the election was. Also, it clarifies the situations and crises after Obama's coming to office with focus on the reforms which Obama made on administration and the Achievements of Obama during his era. Furthermore, it defines the characteristics of the Blacks and how did they live? Did they suffer from racism? And the contribution of the Black minorities politically and economically, also, the major effects of their contribution on American society. The aim of this study is to show and describe the life of the Blacks during Obama's presidency because he was the first African-American president in America and to explain the nature of their contribution in both political and economic sides. Accordingly, a descriptive analytical approach is chosen to carry out this work as it helps in showing the Achievements and reforms of Obama also the contribution in politics and economics that were made by the Black minorities and its effects on the American society.